Temperature-induced phase and microstructural transformations in a synthesized iron carbonate (siderite) complex - Das, Sumanta; Kizilkanat, Ahmet B.; Chowdhury, Swaptik; Stone, David; Neithalath, Narayanan (ELSEVIER SCI LTD, 2016)
The influence of exposure to high temperatures on the phase transformation, microstructural features, and the resultant mechanical properties of a binder based on carbonation of metallic iron powder is reported. The extent of thermal decomposition of the binder at different temperatures is quantified using thermogravimetric analysis (TGA), whereas Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) are used for the identification of transformed phases. High temperature exposure is observed to result in stable phases, which results in the material retaining structural integrity even when exposed to 800 degrees C, contrary to ordinary Portland cement (OPC) pastes that degrade completely at such temperatures. Significant pore size refinement and a small reduction in porosity are noted when the pastes are exposed to high temperatures. Even though there is a significant strength loss when the iron carbonates decompose (around similar to 300 degrees C), the strengths are much higher than those of OPC pastes at higher temperatures. This provides an option for chemistry-based design of high-temperature resistant composites as well as develop structural envelope materials especially when prolonged resistance to more than 600 degrees C is desired. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iron powder; Carbonation; Thermal decomposition; Crystallization; Pore structure; Microstructure; CEMENT-BASED MATERIALS; DIOXIDE CORROSION; MINERAL CARBONATION; CAPTURE CAPACITY; CO2 CAPTURE; MILD-STEEL; PORE; CONCRETE; PASTE; SEQUESTRATION; Materials Science